Seagrass and oyster interactions under a warming climate scenario: A mesocosm experiment - Natalie Schafer; Suzanne Ayvazian; Cathleen Wigand; Kenneth Miller; Donald Cobb; Susanna Osinski (PLoS ONE, 2025)
Seagrass and oyster beds are biogenic habitats of global importance in shallow coastal waters as they provide critical ecosystem functions. These habitats may be adversely affected by warming trends. Short-term effects and interactions of oysters (presence, absence) and water temperature (ambient or warmed +2 °C) on eelgrass, macroalgae, chlorophyll a concentration, and water quality were simulated in mesocosms. Eelgrass ( Zostera marina ) biomass and chlorophyll a concentrations were significantly reduced under elevated water temperature. There were no short-term (9-weeks) effects of oyster ( Crassostrea virginica ) presence on eelgrass biomass, chlorophyll a concentration, nutrients, dissolved inorganic carbon, or dissolved organic carbon. Hourly records of water temperature and light showed an apparent oyster effect with significantly lowered temperatures in the warmed mesocosms and increased light transmittance in warmed and ambient mesocosms for some parts of the day. Surface-only macroalgae were significantly greater in the oyster mesocosms under both warmed and ambient conditions at the end of the experiment than in the eelgrass only mesocosms. In addition, macroalgal coverage (3-dimensional estimate) throughout the mesocosm showed a greater presence in the mesocosms with both oysters and elevated temperatures. A possible outcome of this finding was attenuation of warming, possibly by shading, in the warmed mesocosms. By extension, interactions of oysters and macroalgae may play a role in mitigating warming water temperature in some shallow coastal habitats, highlighting the importance of considering the interactive effects of seagrass and oysters, and other biotic components such as macroalgae, when investigating climate impacts on coastal ecosystems.